PERANCANGAN SISTEM INFORMASI DASHBOARD TIKET LAYANAN HELPDESK CUSTOMER CARE CONTROL CENTER (C4) CONSUMER - Ahmad Nidzom Hilmi; Edhi Prayitno; Juarni Siregar (Journal of Innovation And Future Technology, 2025)
The C4 Consumer Helpdesk Service is one of the business units at PT Infomedia Nusantara, responsible for managing customer complaints and ticketing processes through various communication channels. In response to challenges such as suboptimal responsiveness and a significant percentage of unresolved complaints, this study aims to evaluate and enhance the effectiveness of the helpdesk service. The research adopts the Waterfall software development methodology, encompassing requirement analysis, system design, implementation, testing, and maintenance. The system is developed using PHP and MySQL and is designed to support two user roles: admin and agent. The process begins when customer complaints are received via Telkom's frontliners—Plasa Telkom, Contact Center 147, IndihomeCare social media, or the MyIndihome application—and are then entered into the ticketing system by agents. The system generates a service ticket number, improving on the previous manual process. The research findings demonstrate that the implementation of a web-based information system contributes to a more efficient and structured ticket handling process. It is expected that this system will enhance response times, support real-time service monitoring, and improve overall service quality and agent productivity in alignment with customer expectations.